HaBIT Note: A Notepad and Image to Text Converter Application - Lee, Zi Hui; Ahmad Shaubari, Ezak Fadzrin (Applied Information Technology And Computer Science, 2023)
Today’s advanced society has embraced digital note-taking, with the emergence of digital devices. In productivity applications, Optical Character Recognition (OCR) technology is widely used to facilitate efficient workflow. Most existing note-taking applications have offered vast features and compelling built-in tools to support note-taking, however, these complex features make it unfavourable for beginners. This situation may lead to poor user experiences. Hence, a simple and intuitive note-taking application is proposed to guide students (users) aged 18 to 23 through some of the most basic features of an ideal digital notepad. The Agile methodology has been adapted to develop this minimalist Android-based notepad and image-to-text converter application using Flutter and Firebase. Based on the user (Beta) acceptance test result, this proposed application received 96.99% positive feedback. Overall, this application can be a digital efficiency or supplemental tool to help users in recording key points/ideas on the go, for personal and educational purposes. A further study with a focus on new application features, responsive designs and handwriting recognition is therefore recommended.